Optogenetic control of phosphoinositide metabolism - Idevall-Hagren, Olof; Dickson, Eamonn J; Hille, Bertil; Toomre, Derek K; De Camilli, Pietro (Proceedings of the National Academy of Sciences - PNAS, 2012)
Phosphoinositides (PIs) are lipid components of cell membranes that regulate a wide variety of cellular functions. Here we exploited the blue light-induced dimerization between two plant proteins, cryptochrome 2 (CRY2) and the transcription factor CIBN, to control plasma membrane PI levels rapidly, locally, and reversibly. The inositol 5-phosphatase domain of OCRL (5-ptase(OCRL)), which acts on PI(4,5)P(2) and PI(3,4,5)P(3), was fused to the photolyase homology region domain of CRY2, and the CRY2-binding domain, CIBN, was fused to plasma membrane-targeting motifs. Blue-light illumination (458-488 nm) of mammalian cells expressing these constructs resulted in nearly instantaneous recruitment of 5-ptase(OCRL) to the plasma membrane, where it caused rapid (within seconds) and reversible (within minutes) dephosphorylation of its targets as revealed by diverse cellular assays: dissociation of PI(4,5)P(2) and PI(3,4,5)P(3) biosensors, disappearance of endocytic clathrin-coated pits, nearly complete inhibition of KCNQ2/3 channel currents, and loss of membrane ruffling. Focal illumination resulted in local and transient 5-ptase(OCRL) recruitment and PI(4,5)P(2) dephosphorylation, causing not only local collapse and retraction of the cell edge or process but also compensatory accumulation of the PI(4,5)P(2) biosensor and membrane ruffling at the opposite side of the cells. Using the same approach for the recruitment of PI3K, local PI(3,4,5)P(3) synthesis and membrane ruffling could be induced, with corresponding loss of ruffling distally to the illuminated region. This technique provides a powerful tool for dissecting with high spatial-temporal kinetics the cellular functions of various PIs and reversibly controlling the functions of downstream effectors of these signaling lipids.